Firm‐Level Analysis Using the ABS' Business Longitudinal Analysis Data Environment (BLADE). (1st March 2018) - Hansell, David; Rafi, Bilal
Abstract: The Australian Bureau of Statistics' (ABS) Business Longitudinal Analysis Data Environment (BLADE) is the most comprehensive firm‐level statistical asset in Australia. This short overview provides readers a window into what data sources are used, how they are integrated, current and future applications and how these can contribute to evidence‐based policy making in Australia. At present, direct access is limited to staff directly employed by the Australian Statistician or through secondment.